Bioremediation of Restaurant Wastewater using Immobilized Green Microalgae, (Botryococcus Sp.) on Sequence Batch Reactor Storage Design - Apparao, Y.; Apandi, N.M.; Sunar, N.M.; Ariffin, S.N.H.; Nagarajah, R.; Afifee, R.; Moganathan, S.; Pietrusiewicz, P. (2025)
Wastewater is produced by natural biological processes and a variety of human activities. It is unfit to use directly as the wastewater contains variety of chemicals, contaminants, and pollutants. Wastewater is categorized into two groups of sources which are greywater and blackwater as they differ in contamination levels. Greywater are from showers, baths, whirlpool tubs, washing machines, dishwashers and sinks except for the kitchen sink while the sources of black water are from toilets and kitchen sinks. This study aims to design a Sequence Batch Reactor (SBR) equipped with microalgae microbeads (Botryococcus sp.), to examine the applicability of SBR technology in greywater treatment specifically evaluating the efficiency of SBR performance and to measure the efficiency in removing pollutant greywater of microalgae beads. This was done with the application of SBR to ensure the greywater are properly treated before being discharged.